Student roles in Islamic anti-corruption education: a case study at a Muhammadiyah elementary school - Ilmiatus Soleha; Suyitno (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2026)
Anti-corruption education is widely promoted to foster integrity; however, it is often framed as a normative transmission of values, overlooking how students actively participate in shaping ethical practices. This study addresses this gap by examining student roles in Islamic anti-corruption education within a primary school. This qualitative case study was conducted at Muhammadiyah Kayen Condong catur Elementary School, Yogyakarta, involving 28 students, the principal, and two ISMUBA teachers. Data were collected through in-depth interviews, classroom observations, and document analysis, and analyzed using the Miles and Huberman interactive model to identify patterns of student engagement. The findings show that anti-corruption values are enacted through daily religious practices and school routines rather than formal instruction alone. Students demonstrate a clear distinction between responsibility as procedural compliance and amanah as a spiritually grounded obligation. Importantly, students act as peer monitors who actively regulate dishonest behavior, supported by habituation mechanisms such as the honesty canteen and structured worship activities. This study conceptualizes anti-corruption education as a participatory and practice-based process, highlighting student agency in sustaining school integrity culture and offering insights for designing context-sensitive character education in faith-based schools.